Conceptual measure of oral health literacy level among patients visiting a private dental institution in Dharwad: A cross-sectional questionnaire study - Sheetal Rai; M Shodan; Preetha J Shetty (Wolters Kluwer Medknow Publications, 2015)
Introduction: Oral health literacy (OHL) is the ability of an individual to function independently in certain areas of oral health care activity. It has now evolved as an important determinant of oral health related behavior and practices in any population thus affecting a person's health outcome. Aim: To assess the OHL levels among the sample of a population visiting private dental college and hospital in Dharwad. Materials and Methods: A cross-sectional questionnaire study was conducted on patients visiting a private dental college and hospital in Dharwad. Data was collected from 225 subjects through questionnaire related to five different areas of health care activity. Responses were scored on a dichotomous scale. Analysis of variance and independent t-test were used. Results: Among the study population, 67.6% had medium OHL levels, 24.9% had low, and only 7.6% had high OHL level. OHL had a significant association with age and educational qualification (P < 0.05), whereas gender had no significant association (P < 0.05). Conclusion: Majority had an OHL of medium level as age advanced OHL was lower. As the educational qualification was higher, OHL also improved. This makes education an important parameter in improving the OHL. There is a need to consider OHL while planning future oral heath related programs for this population.